Bradyrhizobium sp. enhance ureide metabolism increasing peanuts yield - Gericó, Thais Grassi [UNESP]; Tavanti, Renan Francisco Rimoldi [UNESP]; de Oliveira, Sandra Cristina [UNESP]; Lourenzani, Ana Elisa Bressan Smith [UNESP]; de Lima, Jéssica Pacheco [UNESP]; Ribeiro, Rodolfo Pires; dos Santos, Leandro Cesar Cusim; dos Reis, André Rodrigues [UNESP] (Springer Nature, 2020)
This study aimed to evaluate the effects of seed inoculation with Bradyrhizobium sp. and co-inoculation with Azospirillum brasilense. The seed treatments were as follows: control (without inoculation); A. brasilense (2 mL per kg−1 of seed); A. brasilense (4 mL per kg−1 of seed); Bradyrhizobium sp. (2 mL per kg−1 of seed); Bradyrhizobium sp. (4 mL per kg−1 of seed); A. brasilense + Bradyrhizobium sp. (2 mL of each strain per kg−1 of seed); and A. brasilense + Bradyrhizobium sp. (4 mL of each strain per kg−1 of seed). Peanut plants from seeds inoculated with Bradyrhizobium sp. and A. brasilense exhibited highest leaf concentration of photosynthetic pigments, carotenoids, nitrate, ammonia and amino acids. The inoculation of seeds with Bradyrhizobium sp. resulted in plants with increased concentrations of total soluble sugars, and ureides compared to the untreated plants. In contrast, seeds treated with A. brasilense alone resulted in plants exhibiting highest concentration of amino acids, which represent the highest concentration of nitrogen compounds in peanut plants. Seed inoculation with Bradyrhizobium sp. at a rate of 2 mL kg−1 was identified as the best treatment to promote increased biological nitrogen fixation and generate higher peanut yields.
Keywords: Arachis hypogaea L; Growth-promoting bacteria; Nitrogen metabolism; Photosynthetic pigments; Seed inoculation